Artificial Intelligence in Legal Decision-Making: an Islamic Law Perspective - Helma Widya; Hermansyah Alam (INFOKUM, 2026)
Artificial Intelligence (AI) has rapidly transformed legal systems by enhancing legal research, case analysis, predictive analytics, and judicial decision-support processes. Despite these advancements, the integration of AI into legal decision-making raises significant ethical, legal, and religious concerns, particularly regarding transparency, accountability, fairness, and conformity with Islamic legal principles. This study examines the application of AI in legal decision-making from the perspective of Islamic law, with particular emphasis on the principles of Maqasid al-Shariah and the objectives of justice (al-'adl), public interest (maslahah), and the prevention of harm (dar' al-mafasid). Using a qualitative normative legal research approach, this study analyzes primary Islamic legal sources, including the Qur'an, Sunnah, classical jurisprudence, contemporary fatwas, and relevant legal and technological literature. The findings indicate that AI can serve as an effective decision-support tool in legal processes by improving efficiency, consistency, and access to justice. However, AI should not replace human judicial authority because Islamic law requires moral reasoning, contextual interpretation (ijtihad), and ethical accountability, which remain exclusive human responsibilities. Furthermore, AI systems employed in legal contexts should satisfy fundamental Shariah principles, including transparency, explainability, fairness, non-discrimination, data privacy, and human oversight. Based on these findings, this study proposes an Islamic legal governance framework for AI-assisted legal decision-making that integrates technological innovation with the ethical objectives of Maqasid al-Shariah. The proposed framework contributes to the development of trustworthy, accountable, and Shariah-compliant AI systems for future legal institutions, particularly in Muslim-majority jurisdictions.